Toward a Feasible Solution for Removing Toxic Mercury and Chromium From Water Using Copper Oxide Nanoparticles - Raul, Prasanta K.; Das, Bodhaditya; Umlong, Iohborlang M.; Devi, Rashmi Rekha; Tiwari, Gaurav; Kamboj, Dev Vrat (Frontiers in Nanotechnology, 2022)
Objective: Water contaminated with heavy metals causes serious environmental issues for people. Mercury and chromium are the notorious nuisance for public health. Diversified technologies have been introduced to purify contaminated water, but a few become successful to reduce mercury and chromium below the permissible limit of drinking water (0.001 ppm and 0.05 ppm respectively, WHO/BIS Guidelines). Our main aim is to synthesize suitable nanoscale materials to make water potable by removing remove mercury and chromium from contaminated water keeping essential elements as per guidelines of WHO/BIS. Methods: Copper(II) Oxide nanomaterials have been synthesized following wet chemical process as per earlier reported procedure. Rod shaped nanoparticles with sizes less than 50 nm are found. XRD confirms formation of rhombohedral CuO nanoparticles. Results: The nanoparticles are efficient to remove mercury from 200 ppb to less than 50 ppb (75%) and chromium from 200 ppb to less than 16 ppb (92%) respectively over wide range of pH. Conclusions: The nanomaterials have the great potential to remove toxic heavy metals from contaminated water. The materials can be applied to integrated water purification system to get potable water.